La costruzione del concetto di omologia e i vincoli materiali della forma - Salvatore Tedesco (Rivista di Estetica, 2016)
The concept of homology is a key component of contemporary theoretical biology because around it and through it numerous joint research projects aims to rethink the centrality of the organism, its evolutionary paths and the significance of its interaction with the environmental reality. The network of homologies that weaves the organismal form allows to structure and channel its morphological and functional innovations. Even this systemic component makes homology a fundamental concept for a dynamic consideration of the living form, like that sought by an aesthetics that does not intend to limit itself to investigate aesthetic attitude and the artistic productions, but knows how to tackle questions related to the more comprehensive question (eminently elaborated from the morphological traditional) of the unity of action and perception as aesthetic configuration of the living being.This study offers a survey of some of the key moments of the historical foundation of the concept of homology, from Goethe's botanical research and their significance in the whole project of Goethe's morphology, to continue with the elaboration of the concept of “anatomical element” by Geoffroy Saint-Hilaire and its problematic (or even misleading) reinterpretation by Arthur Schopenhauer, leading up to the foundation of the modern concept of homology with Richard Owen, in connection with the concept of analogy and the elaboration of the concept of “vertebrate archetype”. In conclusion, this study aims to identify some maior interest of the concept and the theoretical potentialities that find expression in it, between morphological perspective and attention to the material constraints of the form.